Massage in the application of perioperative medicine: research hotspots and trends - Li, Xiaoqin; You, Chuan; Wei, Haige; Li, Huan; Liang, Yun (Frontiers in Medicine, 2025)
BackgroundOver the past decade, the application of massage in the perioperative period has attracted the interest of researchers worldwide, with a relatively stable volume of literature published annually.ObjectiveBy conducting a bibliometric analysis of the literature from the past decade, this study aims to identify the research overview, hotspots, and trends of massage in perioperative medicine.MethodsA search was conducted in the Web of Science Core Collection for literature on the application of massage in perioperative medicine from 2014 to 2024. Articles and reviews were collected with a language restriction to English. Bibliometric and visual analyses were conducted using Co-Occurrence, R Studio, VOSviewer, and Scimago Graphica software.ResultsA total of 434 literature records were retrieved, and after data cleaning (removal of duplicates and incomplete entries), 344 articles were ultimately included. Overall, the number of publications showed a fluctuating upward trend annually. The United States leads in publication volume and has established considerable collaboration with Europe and Brazil, while China ranks second in publication volume but lacks international collaboration. Research primarily focuses on the management of pain and anxiety symptoms, including the improvement of quality of life for patients with somatic diseases and oncological conditions. Cutting-edge topics primarily focus on the efficacy verification of massage techniques and the specific areas targeted, particularly acupoint massage.ConclusionThis study summarizes the research status, hotspots, and trends of massage in perioperative medicine over the past decade, which may aid researchers in gaining a better understanding of this field. China should strengthen international collaboration to promote the development of this field. The efficacy verification of massage techniques and areas, particularly acupoint massage, will be a focal point for future research.